Synthesis of chromium substituted nano particles of cobalt zinc ferrites by coprecipitation - Sharma, R. K.; Suwalka, O.; Lakshmi, N.; Venugopalan, K.; Banerjee, Abhik; Joy, Pattayil Alias (Materials Letters, 2005)
Nano particles of chromium substituted cobalt zinc ferrite have been synthesized by a chemical co-precipitation method. X-ray diffraction studies of the nano particles of CrxCo0.5-xZn0.5Fe2O4 (x = 0.1 to 0.5) heat-treated at 300 degrees C show that the particle sizes are in the range of 2 to 7 nm. Room temperature Fe-57 Mossbauer spectra of all the samples show only two doublets, confirming the presence of superparamagnetic relaxation in the nano particles. An exponential decrease in the superparamagnetic blocking temperature, with increasing chromium concentration, is observed for these samples. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Co0.5Zn0.5Fe2O4; Mossbauer spectroscopy; nano materials

Selectivity tailoring in liquid phase oxidation over MWNT-Mn3O4 nanocomposite catalysts - Biswal, Mandakini; Dhas, Vivek V.; Mate, Vivek R.; Banerjee, Abhik; Pachfule, Pradip; Agrawal, Kanika L.; Ogale, Satishchandra B.; Rode, Chandrashekhar V. (Journal of Physical Chemistry C, 2011)
Highly selective multiwalled nanotubes (MWNT)-Mn3O4 nano-composite catalyst was designed for liquid phase oxidation of p-cresol, which gave highest selectivity of 90% to the first step oxidation product, p-hydroxy benzyl alcohol. Mn3O4 nanoparticles and MWNT-Mn3O4 nanocomposites were synthesized by coprecipitation route using mixed precursors under controlled conditions. The phase purity of Mn3O4 and the formation of MWNT-Mn3O4 nanocomposites were confirmed by X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. High-resolution transmission electron microscopy revealed the selective exposure of (101) and (001) planes of Mn3O4 nanoparticles in the MWNT-Mn3O4 composite, while lowering in oxidizing capacity of MWNT-Mn3O4 nanocomposite confirmed by cyclic voltametry was due to incorporation of electron rich MWNT. Thus, selectivity tuning of the new material (MWNT-Mn3O4 nanocomposite) was found to be due to alteration in both geometric as well as electronic properties. A plausible reaction pathway also has been proposed involving the predominant role of nucleophilic lattice oxygen (O2-) species due to exposure of particular crystal planes giving highest selectivity to p-hydroxy benzyl alcohol.

3D Hexaporous carbon assembled from single-layer graphene as high performance supercapacitor - Yadav, Prasad; Banerjee, Abhik; Unni, Sreekuttan; Jog, Jyoti Prakash; Kurungot, Sreekumar; Ogale, Satishchandra (Chemsuschem, 2012)
Keywords: Electrochemistry; Energy storage; graphene; porous materials; Supercapacitors

Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

MOF derived porous carbon-Fe3O4 nanocomposite as a high performance, recyclable environmental superadsorbent - Banerjee, Abhik; Gokhale, Rohan; Bhatnagar, Sumit; Jog, Jyoti Prakash; Bhardwaj, Monika; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Materials Chemistry, 2012)
A high surface area carbon composite with Fe3O4 nanoparticles is synthesized by pyrolysis of an iron containing Metal Organic Framework (MOF). The composite can be prepared by annealing the MOF at different temperatures (500 degrees C and 600 degrees C), each case exhibiting unique properties in terms of the hydrophobic behaviour and surface area, resulting in specific applicability domains. We highlight the exceptional behaviour of this material as a magnetically separable and recyclable superadsorbent for removal and recovery of environmental pollutants (oil/hydrocarbon and dye/phenol).

Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.

Hollow Co0.85Se nanowire array on carbon fiber paper for high rate pseudocapacitor - Banerjee, Abhik; Bhatnagar, Sumit; Upadhyay, Kush Kumar; Yadav, Prasad; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2014)
A supercapacitor electrode is fabricated with Co0.85Se hollow nanowires (HNW) array, which is synthesized by wet chemical hydrothermal selenization of initially grown cobalt hydroxyl carbonate nanowires on conductive CFP. The dense self-organized morphology of Co0.85Se HNWs is revealed by scanning/transmission electron microscopy. The as-synthesized Co0.85Se HNWs possess high pseudocapacitive property with high capacitance retention and high durability. The areal capacitance value is seen to vary from 929.5 to 600 mF cm(-2) (60% retention) as the current density is increased from 1 to 15 mA cm(-2), an increase of a factor of 15. Based on mass loading, this corresponds to a very high gravimetric capacitance of 674 (for 2 mA cm(-2) or 1.48 Ag-1) and 444 Fg(1-) (for 15 mA cm(-2) or 11 A g(-1)) in a full-cell configuration with the Co0.85Se HNWs as cathode and activated carbon as anode (asymmetric configuration) promising results are obtained.
Keywords: asymmetric supercapacitor; carbon fiber paper; cobalt selenide; hydrothermal; pseudocapacitor; selenization

MOF-derived crumpled-sheet-assembled perforated carbon cuboids as highly effective cathode active materials for ultra-high energy density Li-ion hybrid electrochemical capacitors (Li-HECs) - Banerjee, Abhik; Upadhyay, Kush Kumar; Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Nanoscale, 2014)
Lithium ion hybrid capacitors (Li-HECs) have attracted significant attention for use in next generation advanced energy storage technologies to satisfy the demand of both high power density as well as energy density. Herein we demonstrate the use of very high surface area 3D carbon cuboids synthesized from a metal-organic framework (MOF) as a cathode material with Li4Ti5O12 as the anode for high performance Li-HECs. The energy density of the cell is similar to 65 W h kg(-1) which is significantly higher than that achievable with commercially available activated carbon (similar to 36 W h kg(-1)) and a symmetric supercapacitor based on the same MOF-derived carbon (MOF-DC similar to 20 W h kg(-1)). The MOF-DC/Li4Ti5O12 Li-HEC assembly also shows good cyclic performance with similar to 82% of the initial value (similar to 25 W h kg(-1)) retained after 10 000 galvanostatic cycles under high rate cyclic conditions. This result clearly indicates that MOF-DC is a very promising candidate for future P-HEVs in a Li-HEC configuration.

Nickel cobalt sulfide nanoneedle array as an effective alternative to pt as a counter electrode in dye sensitized solar cells - Banerjee, Abhik; Upadhyay, Kush Kumar; Bhatnagar, Sumit; Tathavadekar, Mukta; Bansode, Umesh P.; Agarkar, Shruti A.; Ogale, Satishchandra B. (RSC Advances, 2014)
Self supported nickel cobalt sulfide (NCS) nanoneedles are directly formed on FTO glass substrates by sulphurization of nickel cobalt oxide nanoneedles (grown by a hydrothermal method) in the presence of a hydrogen sulfide and argon gas mixture. These NCS nanoneedles when used as a counter electrode for dye sensitized solar cells (DSSCs) show efficient catalytic activity towards the I-/I-3(-) redox couple, and lead to an impressive efficiency of 6.9%, compared with 7.7% obtained with a Pt electrode in similarly constructed devices.

Surfactant free gram scale synthesis of mesoporous Ni(OH)(2)-r-GO nanocomposite for high rate pseudocapacitor application - Singh, Upendra; Banerjee, Abhik; Mhamane, Dattakumar; Suryawanshi, Anil; Upadhyay, Kush Kumar; Ogale, Satishchandra (RSC Advances, 2014)
We report a single-step surfactant-free gram scale hydrothermal synthesis of mesoporous Ni(OH)(2) nanoparticles and the Ni(OH)(2)-reduced graphene oxide (Ni(OH)(2)-r-GO) nanocomposite. Interesting morphological features are noted. These nanomaterials are examined and compared as cathode materials for pseudo-capacitor application through detailed characterizations. A high specific capacitance (C-s) of 1538 F g(-1) is observed for Ni(OH)(2)-r-GO even at a high current density of 40 A g(-1), whereas at the same current rate, bare Ni(OH)(2) shows C-s of only 936 F g(-1).

High surface area porous carbon for ultracapacitor application by pyrolysis of polystyrene containing pendant carboxylic acid groups prepared via click chemistry - Chhatre, Shraddha; Aravindan, Vanchiappan; Puthusseri, Dhanya; Banerjee, Abhik; Madhavi, Srinivasan; Wadgaonkar, Prakash P.; Ogale, Satishchandra B. (Materials Today Communications, 2015)

3D Polyaniline architecture by concurrent inorganic and organic acid doping for superior and robust high rate supercapacitor performance - Gawli, Yogesh; Banerjee, Abhik; Dhakras, Dipti; Deo, Meenal S.; Bulani, Dinesh; Wadgaonkar, Prakash P.; Shelke, Manjusha; Ogale, Satishchandra (Scientific Reports, 2016)

Heteroatom facilitated preparation of electrodes for sodium ion batteries - Bhosale, Manik E.; Banerjee, Abhik; Krishnamoorthy, Kothandam (RSC Advances, 2017)
A conjugated polymer comprising heterocycles was prepared and carbonized to obtain carbon with interlayer spacings between 0.42 and 0.37 nm and exhibited a specific capacity of 250 mA h g(-1).

Mitigating dendrite formation on a Zn electrode in aqueous zinc chloride by the competitive surface chemistry of an imidazole additive - Rana, Ashutosh; Thakare, Anup; Kumar, Nikhil; Mukherjee, Buddhadev; Torris, Arun; Das, Bidisa; Ogale, Satishchandra; Banerjee, Abhik (ACS Applied Materials and Interfaces, 2023)
Electrochemical energy storage systems are critical in several ways for a smooth transition from nonrenewable to renewable energy sources. Zn-based batteries are one of the promising alternatives to the existing state-of-the-art Li-ion battery technology, since Li-ion batteries pose significant drawbacks in terms of safety and cost-effectiveness. Zn (with a reduction potential of -0.76 V vs SHE) has a significantly higher theoretical volumetric capacity (5851 mAh/cm3) than Li (2061 mAh/cm3), and it is certainly far less expensive, safer, and more earth-abundant. The formation of dendrites, hydrogen evolution, and the formation of a ZnO passivation layer on the Zn anode are the primary challenges in the development and deployment of rechargeable zinc batteries. In this work, we examine the role of imidazole as an electrolyte additive in 2 M ZnCl2 to prevent dendrite formation during zinc electrodeposition via experimental (kinetics and imaging) and theoretical density functional theory (DFT) studies. To characterize the efficacy and to identify the appropriate concentration of imidazole, linear sweep voltammetry (LSV) and chronoamperometry (CA) are performed with in situ monitoring of the electrodeposited zinc. The addition of 0.025 wt % imidazole to 2 M ZnCl2 increases the cycle life of Zn-symmetric cells cycled at 1 mA/cm2 for 60 min of plating and stripping dramatically from 90 to 240 h. A higher value of the nucleation overpotential is noted in the presence of imidazole, which suggests that imidazole is adsorbed at a competitively faster rate on the surface of zinc, thereby suppressing the zinc electrodeposition kinetics and the formation. X-ray tomography reveals that a short circuit caused by dendrite formation is the main plausible failure mechanism of Zn symmetric cells. It is observed that the electrodeposition of zinc is more homogeneous in the presence of imidazole, and its presence in the electrolyte also inhibits the production of a passivating coating (ZnO) on the Zn surface, thereby preventing corrosion. DFT calculations conform well with the stated experimental observations.
Keywords: dendrite; Density functional theory; exchange current density; Imidazole; X-ray computed tomography; zinc metal electrodeposition